The quest for responsiveness : Maori policy advisers and the state : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts at Massey University - Gembitsky, Brendan (Massey University, 1992)
This thesis examines the relationship between Maori and the state. In the last quarter of a century, Maori have sought to recover their economic resources and revive their political structures. Gaining access to both the resources and the power of the state have been increasingly seen as important ways in which Maori can do this. This thesis has focused in particular, on Maori policy advisers within the state sector. Through a set of semi-structured interviews Maori policy advisers' views of the state, their role within it and their practices have been explored. The Maori advisers participating in this study maintained a strong relationship to Maori groups outside of the state and a commitment to kaupapa Maori. The tensions this raised and the practices that were used to address those are a central part of this thesis.
Keywords: New Zealand people; Maori; Government relations; Politics and government